Social Studies: Level Two Interaction. Teacher's Guide=Araling Panlipunan: Ikalawang Antas--Pakikisalamuha. Patnubay Ng Guro. - Berkeley Unified School District, CA. Asian American Bilingual Center; Berkeley Unified School District, CA. Asian American Bilingual Center; California State Univ., Los Angeles. National Dissemination and Assessment Center ([S.l.] : Distributed by ERIC Clearinghouse, 1981)
This Pilipino teacher's guide is part of Berkeley, California Unified School District Asian American Bilingual Center's interest in fostering the total growth of the child. To facilitate that growth, the Center has selected an interdisciplinary approach to curriculum development. Social studies themes and concepts provide the framework within which all the subject areas, including mathematics, reading and language arts, fine arts, and science, are organized. The four social studies themes are child, family, community, and natural environment. The themes reappear and expand through the curriculum from one text to the next and correspond with the concepts of identity, needs and interaction. Level Two is designed for children in grades three and four. Each level develops one or more apsect oa a theme as the child moves from simple to complex ideas and from understanding of self to understanding of society. Unit 1 of the document, entitled "The Arts," examines the arts as a means of communication, as comprising many forms, and as an integral part of daily life. Unit 2, "Thoughts and Feelings," explains that interaction requires decision making and problem solving that may involve desirable and undesirable options, and may implicate thoughts and feelings. The document includes an introduction, notes to the teacher, and a resource guide. (SG)
Sponsoring Agency: Department of Education, Washington, DC.
ERIC Note: For related documents in the series, see SO 022 126-135; for the corresponding resource book, see SO 022 129.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aesthetic Education; Affective Behavior; Bilingual Education; Concept Formation; Cultural Interrelationships; Curriculum Development; Elementary Education; Elementary School Curriculum; Filipino Americans; Grade 3.; Grade 4.; Individual Development; Instructional Materials; Interdisciplinary Approach; Learning Activities; Resource Materials; Tagalog; Teaching Guides; Thematic Approach; Guides, Classroom -- Teacher; Multilingual/Bilingual Materials